Ankle fusion percutaneous home run screw fixation: Technical aspects and soft tissue structures at risk. (September 2019) - Roberts, L.; Godoy-Santos, A.L.; Hudson, P.W.; Phillips, S.; Nishikawa, D.R.C.; Shah, A.; de Cesar Netto, C.
Highlights: Sural nerve injury is reported from 0 to 18% in percutaneous ankle procedures. Most studies do not account for all attempts made at wire positioning. The mean number of guidewires needed to achieve an acceptable position was 2.34. The sural bundle was either injured or in direct contact with the guidewires in 73% of the time. Abstract: Introduction: The objective of this cadaveric study was to identify the number of attempts necessary for a perfect positioning of the ankle fusion home run screw and the neurovascular and tendinous structures at risk. Methods: Eleven cadaveric limbs were used. Guidewires were percutaneously placed into the distal posterolateral aspect of the leg, under fluoroscopic guidance, with the ankle held in neutral position. Malpositioned guidewires were not removed and served as guidance for the following wires. The number of guidewires needed to achieve an acceptable positioning of the implant was noted. Neurovascular and tendinous injuries were assessed, and the shortest distance between the closest guidewire and the soft tissue structures was measured using a precision digital caliper. Results: Mean number of guidewires needed to achieve acceptable positioning of the implant was 2.34 (SD 0.81, range 2–4). The mean distances between the closest guide pin and the soft tissue structures of interest were: Achilles tendon 5.35 mm (SD 2.74 mm); peroneal tendons 9.65 mm (SD 5.19 mm); posteromedial neurovascular bundle 12.78 mm (SD 7.14 mm). The sural bundle was in contact with the guide pin in 5/11 specimens (45.5%) and impaled in 3/11 specimens (27.3%). The average distance from the sural nerve bundle was 3.58 mm (SD 2.16 mm). Conclusions: The placement of percutaneous ankle fusion home run screws is technically demanding requiring multiple attempts for acceptable placement. Important tendinous and neurovascular structures are in close proximity to the guidewires. The sural bundle was either injured or in direct contact with the guide wire in approximately 73% of the cases. When using a home run screw, a mini-open approach is recommended. Level of evidence: Level V, cadaveric study.